Kinerja Koperasi Pegawai Negeri Guru Agama Batipuh Ditinjau dari Rasio Likuiditas dan Solvabilitas - Sari, Chitra Indah (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
The objectives of this study are as follows: 1) To find out the performance of the Batipuh KPN-GA seen from the Liquidity Ratio; 2) To find out the performance of the Batipuh KPN-GA seen from the Solvency Ratio. This study took place in the Cooperative Civil Servants Cooperative in Batipuh Subdistrict, Tanah Datar District. The data collected is quantitative data from the RAT Report of the 2014-2018 Batipuh religion teacher civil service cooperative. This type of research is a quantitative approach. Analysis. The performance results of the Bgapuh State Religion Teachers Cooperative Cooperative are seen from the ratio of liquidity and solvency. The liquidity ratio with the current ratio and Quick ratio is quite good because KPN-GA can meet its short-term obligations. The ratio of Solvency to debt to asset ratio and Net worth to Debt Ratio is quite good because KPN-GA can meet its long-term obligations. Based on the results of the study it is recommended that the KPN-GA improve its performance by maintaining the liquidity and solvency ratios so that the sustainability of the cooperative is maintained.